Novel Measures to Assess the Effects of Partial Sleep Deprivation on Sensory, Working, and Permanent Memory - Gosselin, Dominique; De Koninck, Joseph; Campbell, Kenneth (Frontiers in Psychology, 2017)
Sleepiness has repeatedly been demonstrated to affect performance on a variety of cognitive tasks. While the effects of total sleep deprivation have been extensively studied, acute partial sleep deprivation, a much more frequent form of sleep loss, has been studied much less often. The present study examined the effects of sleep deprivation on novel tasks involving classic sensory, working, and permanent memory systems. While the tasks did involve different memory systems, they shared a need for effortful, sustained attention to maintain successful performance. Because of the novelty of the tasks, an initial study of the effects of total sleep deprivation was carried out. The effects of partial sleep deprivation were subsequently examined in a second study, in which subjects were permitted only 4 hours of sleep. A general detrimental effect of both total and partial sleep deprivation on accuracy of detection was observed and to a lesser extent, a slowing of the speed of responding on the different tasks. This overall effect is best explained by the often-observed inability to sustain attention following sleep loss. Specific effects on distinct cognitive processes were also observed, and these were more apparent following total than partial sleep deprivation.